Reimagining spaces, species and societies in the Himalayas - Erik de Maaker (European Bulletin of Himalayan Research)
Himalayan environments have changed, and are changing, due to the ways in which people have interpreted, sourced, and utilised them. Scholarly analysis of the transformations induced, be it in deforestation, dam building or glacial melt, foreground how man is shaping the world in the Anthropocene. Alternatively, multispecies studies have shown how people invariably depend on, and are being shaped, by the dedicated environments in which they find themselves. Rather than people existing independent of these, their lives are the product of ‘co-becoming’ (Country et al 2016: 1) or ‘becoming-with’ (Haraway 2008: 12) a variety of spaces and species. In relation to the Himalayas, the two angles of enquiry outlined above have so far seldom been combined. In an attempt to engage with this lacuna, the contributions to this special issue scrutinise the changing framing and interpretation of human and non-human relationships, and the way these find expression in everyday life. At the same time, the contributions explore how large-scale interventions instigated by state making, development initiatives and the expansion of commercial ventures have transformed, and continue to transform, mountain spaces and species, generating new societal contexts in which these acquire new meanings.